Equivalence between the planar Dirac oscillator and a spin-1/2 fermion embedded in a transverse homogeneous magnetic field - Castro, Antonio Soares De [UNESP] (Sociedade Brasileira de Física, 2019)
It is shown that a spin-1/2 fermion coupled to the axially symmetric electromagnetic vector potential has the same matrix structure as that one for the planar Dirac oscillator. In particular, the planar Dirac oscillator can be interpreted as a charged particle minimally coupled to a transverse homogeneous magnetic field.
Keywords: Dirac oscillator; relativistic planar motion; transverse homogeneous magnetic field